Intraoperative absent bilateral medial recti in syndromic craniosynostosis. Issue 1 (18th January 2021) - Chaurasia, Shweta; Sharma, Pradeep; Surve, Abhidnya; Chaurasia, Swati
Abstract : Patients with syndromic craniosynostosis are usually associated with the complexity of the malformation complex. We describe here detailed oculo-motility disorder and a remarkable finding of hypoplastic bilateral media recti on imaging and its intraoperative absence in patients with phenotypic features resembling Shprintzen-Goldberg syndrome (SGS). SGS is a rare congenital disorder with craniosynostosis affecting multiple systems including mentation and having a considerable overlap of its phenotypic features with Marfan syndrome. Large A-pattern exotropia found in these patients may be related to the craniofacial features and their bearing on extraocular muscle development and function. In this paper, we aimed to sensitise ophthalmologists and strabismologists concerning the necessity to recognise syndromic associations of patients with craniosynostosis presenting with a large squint, be aware of the intraoperative surprises and consider the challenges in its management.